Application of rule association with algorithm apriori of disaster residental fires - Muhajir, Muhammad; Gusmayyeni, Gusmayyeni; Sari, Redita Anggita; Rahmatika, Tusriana (Association for Scientific Computing Electrical and Engineering, 2017)
Data mining is a technique of decision making by means of extracting information based on historical data of existing data in a large database. One of technique in data mining, is association rule algorithm where the method is searching for a set of items that frequently appear together. This study will use data association rule mining method for data processing Fire Disaster settlements in Indonesia because we want to know what information is often occur together in the event of fire disaster settlement. From the analysis associative relationship, event's pattern that occur from residential fires in Indonesia which the data is from the beginning of January 2015 to June 2015, support the highest value that the event of catastrophic fires in settlements in the afternoon resulted in broken homes with a value of 0.8148148 support and confident value of 1.0292398.